2007
DOI: 10.1007/s00264-006-0283-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcondylar traction as a closed reduction technique in vertically unstable pelvic ring disruption

Abstract: Little information is provided in the literature describing an efficient reduction technique for pelvic ring disruption. The aim of this study is to assess the use of the transcondylar traction as a closed reduction technique for vertically unstable fracture-dislocations of the sacro-iliac joint. Twenty-four pelvic ring disruptions were treated with attempted closed reduction followed by percutaneous screw fixation. Transcondylar traction was used as a closed reduction technique. Closed reduction to within 1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…[3][4][5][6][7] Displaced fractures of the pelvic ring in association with vertically unstable disruption of the osteoarticular junction of the sacroiliac area may also require the management by either external fixation, percutaneous or mini-incisional screw fixation, conventional surgical exploration, or a combination of one or more of these procedures. [8][9][10][11][12][13][14] In this regard, several reports described that malunited fractures of the pelvic ring were associated with poor functional outcome. 1,4,5,11,15 In contrast, some authors described no relationship between functional outcome and major displacement of the pelvic ring.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Displaced fractures of the pelvic ring in association with vertically unstable disruption of the osteoarticular junction of the sacroiliac area may also require the management by either external fixation, percutaneous or mini-incisional screw fixation, conventional surgical exploration, or a combination of one or more of these procedures. [8][9][10][11][12][13][14] In this regard, several reports described that malunited fractures of the pelvic ring were associated with poor functional outcome. 1,4,5,11,15 In contrast, some authors described no relationship between functional outcome and major displacement of the pelvic ring.…”
Section: Introductionmentioning
confidence: 99%
“…We have been operating with a radiolucent table till date while treating FFP type IIIa alone and never used a traction table for fracture reduction of this type. A study reported that longitudinal traction is useful for high-energy pelvic ring fractures with vertical instability [ 7 ]. In general, a Kirschner wire is inserted into the femur on the same side as the affected one and withdrawn to reduce it.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a Kirschner wire is inserted into the femur on the same side as the affected one and withdrawn to reduce it. Thus, it is introduced as a reduction technique via transcondylar traction [ 7 ]. The present case was a fracture of the iliac wing from the greater sciatic notch, and the fracture was shortened to the caudal direction with a third bone fragment.…”
Section: Discussionmentioning
confidence: 99%
“…Under such circumstances, the authors propose transcondylar traction at the initial stage, which could reduce the vertical fracture-dislocation, making surgery easier at a later stage. 22 Third, the authors propose reduction of the vertically unstable crescent fracturedislocation via a posterior approach. The advantages include direct visualization and reduction of the fracture-dislocation with the help of reduction forceps.…”
Section: Discussionmentioning
confidence: 99%